Evaluation of the antinociceptive potential of sodium valproate in mice - Lidia Cristina Chitac; Sorin Beschea; Monica Neamtu; Delia Bulea; Veronica Bild (Medicamentul Veterinar)
Recent research in the field of algesiology demonstrated the existence of several types of pain, with complex mediation cascades. This fact prompted the use of compounds from other drug families than classical analgesics for the treatment of pain. The purpose of this paper is to demonstrate the antinociceptive action of sodium valproate in mice. This investigation relies on three nociception models that use chemical, thermal, mechanical (pressure) stimuli, and a model of acute inflammation induced by carrageenan. The investigations were made using male white Swiss mice, weighing 20-30 grams. Valproate administration has been made orally, using geometric progression dose sequences. According to the statistical analysis, we obtained values of ED50 for sodium valproate for each nociception model as follows: ED50 = 21.773 ± 6.786 mg/kg for the nociception model with Zymosan A, ED50 = 11.807 ± 4.035 mg/kg, for the hot plate test, ED50 = 19.247 ± 2.207 mg/kg for the Randall-Sellitto test. The action of the valproate is explained by the inhibition of pro-inflammatory cytokines like TNF-D IL1E, IL6 and prostaglandin mediators like PGE2. The experiments were made according to the European and Romanian legislation that concerns working with lab animals.